RANCANGAN AWAL DAN ANALISIS BENTUK SUDU TURBIN ANGIN 50 KW - Dines Ginting (National Institute of Aeronautics and Space - LAPAN, 2010)
Wind turbine blade design is done through the process of aerodynamic optimization involving wind speed, blades number and profile, solidity and rotor speed. Three options of 50 kW wind turbine blade shape the will be analyzed, the optimum shape, taper and rectangular. Each blade shape has the distinct complexity and characteristics so that the handling and manufacture, the performance characteristic, the diameter and speed of blades is also different. Maximum performance of the optimum blade shape is higher than the tapered or rectangular shapes so that the diameter of the optimum blade shape is smaller than the tapered or rectangular shapes. On the contrary, handling and manufacture blades with square shape easier than with any shape optimum or taper. The different blade shapes will not cause any disadvantage as far as handling and manufacture of blades that means the blade cost to compensate for this blade shapes effect. The taper blade shape is selected for the wind turbine. Key words: Aerodynamic design, Wind turbine blade shape, Performance characteristics